2017
DOI: 10.4103/ija.ija_86_17
|View full text |Cite
|
Sign up to set email alerts
|

A randomised comparative study of Miller laryngoscope blade versus Oxiport® Miller laryngoscope blade for neonatal and infant intubations

Abstract: Background and Aims:Neonates and infants are prone to oxygen desaturation during the induction of general anaesthesia. Pharyngeal oxygen insufflation has been shown to delay the onset of desaturation and hypoxaemia during apnoea. We tested the hypothesis that deep laryngeal oxygenation with Oxiport® Miller blade would delay the onset of desaturation compared to laryngoscopy without supplemental oxygen (Miller blade).Methods:One hundred neonates and infants undergoing general anaesthesia with endotracheal intub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…The possibility of supplying oxygen via a laryngoscope is not entirely new and has been described by others. Using a Miller-shaped blade in neonates has shown to decrease the incidence of severe desaturation during neonatal and infant intubations in a study by Dias et al [ 15 ] However, the use of Miller-shaped blades outside the neonatological and pediatric setting is extremely rare. Since the Macintosh blade type is standard and the by far most widespread laryngoscope type in Europe, we decided to create a modified Macintosh blade.…”
Section: Discussionmentioning
confidence: 99%
“…The possibility of supplying oxygen via a laryngoscope is not entirely new and has been described by others. Using a Miller-shaped blade in neonates has shown to decrease the incidence of severe desaturation during neonatal and infant intubations in a study by Dias et al [ 15 ] However, the use of Miller-shaped blades outside the neonatological and pediatric setting is extremely rare. Since the Macintosh blade type is standard and the by far most widespread laryngoscope type in Europe, we decided to create a modified Macintosh blade.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the actual study, the base of the tongue may be described as a turning point for oxygen insufflation in the human airway, completely avoiding any ambient air from entering the airway. This effect may be reached by different devices such as an oxygenation laryngoscope or a special oropharyngeal oxygenation airway device [3,4,17,18]. The value of the placement of these devices at the base of the tongue must be evaluated both in animal and clinical studies in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence summary: Five RCTs have shown that supplemental oxygen increases the safe apnoea time in neonates and infants and reduces the incidence of hypoxaemia during tracheal intubation (Supplementary Table S6, http://links.lww.com/EJA/A891). [45][46][47][48][49] Supplemental oxygen can be delivered directly via the airway instrumentation device AirTraq (Prodol Meditec S.A., Vizcaya, Spain), Truview (Truphatek International Ltd, Netanya, Israel), Oxiport (Truphatek International j , Israel), nasopharyngeal airway or via nasal cannula.…”
Section: Pico 3 Tracheal Intubation Is Direct Laryngoscopy or Videola...mentioning
confidence: 99%